The effects of actual human size display and stereoscopic presentation on users' sense of being together with and of psychological immersion in a virtual character - Ahn, Dohyun (2015)
This study examined the role of display size and mode in increasing users' sense of being together with and of their psychological immersion in a virtual character. Using a high-resolution three-dimensional virtual character, this study employed a 2×2 (stereoscopic mode vs. monoscopic mode×actual human size vs. small size display) factorial design in an experiment with 144 participants randomly assigned to each condition. Findings showed that stereoscopic mode had a significant effect on both users' sense of being together and psychological immersion. However, display size affected only the sense of being together. Furthermore, display size was not found to moderate the effect of stereoscopic mode.